Solon if Athens – citizenship and paideia - Barros, Gilda Naécia Maciel de (2011)
Solon was the first to extol the ideal of citizenship, basing his idea on two essential values: political participation and repudiation of tyranny. As leader of the city in its crisis, he established essential reforms to lead Athens to good order (eunomia) This article extols the man of wisdom, legislator and political reformer who finally teaches us the relationship between human happiness and the political life worth living.